2008
DOI: 10.1007/s10549-008-0252-6
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of early breast cancer management in relation to patient and hospital characteristics: a population based study in Northern Italy

Abstract: Administrative data may provide valuable information for monitoring the quality of care at population level and offer an efficient way of gathering data on individual patterns of care, and also to shed light on inequalities in access to appropriate medical care. The aim of the study was to investigate the role of patient and hospital characteristics in the initial treatment of early breast cancer using administrative data. Incident breast cancer patients were identified from hospital discharge records and link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
(29 reference statements)
3
23
0
Order By: Relevance
“…Moreover, longitudinal data trends, like the above presented, could provide a valuable assessment and feedback tool in the case where an intervention to counteract patient migration took place, e. g., a new oncology-specific structure has been added in the district or an existing one was upgraded. Taking into account the international perspective, the findings of the present study are in line with reports from the literature that document that geography presents a serious barrier to adequate treatment for cancer both in countries with an established National Health Service [27][28][29], like the case presented in this paper, as well as for countries with "less centralized" types of health services provision [30,31]. The analysis of patient mobility could apply for both types of service provision and produce important findings as to the responsiveness of the system, or the financial burden placed upon patients or healthcare budgets, as a result of unmet needs for inelastic demands, like cancer treatment, or treatment for other life-threatening diseases.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, longitudinal data trends, like the above presented, could provide a valuable assessment and feedback tool in the case where an intervention to counteract patient migration took place, e. g., a new oncology-specific structure has been added in the district or an existing one was upgraded. Taking into account the international perspective, the findings of the present study are in line with reports from the literature that document that geography presents a serious barrier to adequate treatment for cancer both in countries with an established National Health Service [27][28][29], like the case presented in this paper, as well as for countries with "less centralized" types of health services provision [30,31]. The analysis of patient mobility could apply for both types of service provision and produce important findings as to the responsiveness of the system, or the financial burden placed upon patients or healthcare budgets, as a result of unmet needs for inelastic demands, like cancer treatment, or treatment for other life-threatening diseases.…”
Section: Discussionsupporting
confidence: 90%
“…Some studies have shown that determinants related to health care, such as unequal access to treatment, are important factors in the differences in the survival rates of cancer patients by socio-economic status [14]. For example, disadvantages in receiving timely treatment or breast, colorectal or lung cancer surgery among less educated or poor (with lower income) individuals or people living in socio-economically deprived areas have been reported in Italy, England, and Denmark [21][22][23][24]. Evidence from Denmark suggests that substantial socio-economic differences also exist in cancer rehabilitation and this may contribute to the observed disparities in cancer survival [25].…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanism for the volume-outcome relationship in breast cancer remains unclear and may be influenced by a number of factors including surgeon volume [3][4][5][6][7], hospital volume [6,[8][9][10][11][12][13][14][15][16][17][18], level of specialization of both the provider and hospital [5,[19][20][21], teaching status of the hospital [13,22,23], and processes of care [11,[14][15][16]24]. Several studies have attempted to attribute the hospital volume-outcome relationship in breast cancer to differences in processes of care.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in one study using data from the Nationwide Inpatient Sample database, higher volume hospitals were associated with increased use of breast-conserving surgery [14]. These & Amanda L. Kong akong@mcw.edu studies have examined individual processes of care in isolation with respect to their effect on hospital volume and outcomes [11,[14][15][16]. The purpose of this study was to examine differences in patterns of care among breast cancer patients treated in high-and lower-volume hospitals as a possible explanation for the well-documented differences in survival among patients treated at these hospitals.…”
Section: Introductionmentioning
confidence: 99%